How to allocate research (and other) subsidies - Ludwig Ensthaler; Thomas Giebe (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
A budget-constrained buyer wants to purchase items from a shortlisted set. Items are differentiated by observable quality and sellers have private reserve prices for their items. The buyer's problem is to select a subset of maximal quality. Money does not enter the buyer's objective function, but only his constraints. Sellers quote prices strategically, inducing a knapsack game. We derive the Bayesian optimal mechanism for the buyer's problem. We find that simultaneous takeit-or-leave-it offers are optimal. Hence, somewhat surprisingly, ex-post competition is not required to implement optimality. Finally, we discuss the problem in a detail free setting.
Keywords: D21; D44; D45; D82; 330; Mechanism Design; Subsidies; Budget; Procurement; Knapsack Problem; Forschungssubvention; Beschaffung; Mechanism Design; Verschuldungsrestriktion; Dienstleistungsqualität; Produktdifferenzierung; Ganzzahlige Optimierung; Spieltheorie; Theorie